Failure mechanism of the Y2O3 doped BaZrO3/Al2O3 composite ceramic mould during directional solidification of TiAl-Based alloys. Issue 4 (15th February 2022) - Duan, Baohua; Feng, Qisheng; Jiao, Lina; Zhang, Xuexian; Mao, Lu; Xiong, Fuhao; Yang, Yuchen; Lu, Xionggang; Chen, Guangyao; Li, Chonghe
Abstract: Directional solidification of Ti–46Al–8Nb (at.%) intermetallic in the Y2 O3 doped BaZrO3 /Al2 O3 composite ceramic mould was carried out using Bridgman apparatus. To increase the success rate of Ti–46Al–8Nb single crystals preparation and improve the quality of the ingots, the failure mechanism of the mould in directional solidification experiments was evaluated. Nucleation and propagation of cracks in the moulds were investigated by tracing each key process of the experiment, the effect of pores in the mould on the target alloy was revealed by studying the mould/metal interface. The results show that the macrocracks in the facecoat of the mould would lead to the leakage of the alloy melt. Furthermore, the alloy melt would infiltrate into the mould through large-size pores, which would increase the oxygen content of the target alloy, and also form inclusions containing O, Zr, Si and Y elements in the alloy ingot. Highlight: Macrocracks in the primary facecoat of the mould will lead to the leakage of the alloy melt. The alloy melt will not cause cracks on the primary facecoat of the mould, but only expand the original cracks. The alloy melt first infiltrates along the large size pores, and then spreads around along the cracks to small size pores. (Zr, Si)-containing inclusions are mainly caused by the segregation of impurity elements in the γ-TiAl matrix phase. Y-containing inclusions are caused by the insoluble Y2 O3  particles, and its chemical composition may be (Y, Al)2 O3 .